Efficacy of Petai (Parkia speciosa, HASSK) leaf extract as an antidyslipidemic herb in Rattus norvegicus induced by high-fat feed - Jatmiko Susilo; Anita Widya Astuti; Dewi Larasati (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2020)
This study aims to analyze the effect of Petai (Parkia speciosa, HASSK) leaf extract on total cholesterol, triglycerides, LDL and HDL levels in dyslipidemic rat models induced high-fat feed. The pre and post-test with control group design using 30 rats were divided into 5 groups, namely positive, normal, and Petai leaf extract at doses of 100, 200 and 400 mg/kg BW. All rats were fed high fat diet for 14 days. The extract group was given Petai leaf extract orally from day 14 to day 28. Lipid profiles were tested using enzymatic spectrophotometry method. Petai leaf extract was identified to contain flavonoid compounds. The research showed that the Petai leaf extract at a dose of 100, 200 and 400 mg / kg BW  were able to decrease total cholesterol: (-32.06 ± 3.63), (-47.23 ± 2.98), and (-49,18 ± 2.66), mg / dL; triglyceride: (-11.12 ± 3.99), (-37.31 ± 0.65), and (-43.01 ± 1.17) mg / dL; LDL: (-17.14 ± 9.30), (-46.51 ± 1.99), and (-46.51 ± 1.99) mg / dL; and increasing HDL levels: (6.44 ± 0.21), (8.42 ± 0.73), and (12.1 ± 0.43) mg / dL respectively. This study proves that Petai leaf extract has anti-dyslipidemic activity in rat models by reducing total cholesterol, triglycerides, and LDL and increasing HDL levels.